Genetic Polymorphisms and Kidney Stones Around the Globe: A Systematic Review and Meta-Analysis - Mohammadi, Abdolreza; Shabestari, Alireza Namazi; Baghdadabad, Leila Zareian; Khatami, Fatemeh; Reis, Leonardo Oliveira; Pishkuhi, Mahin Ahmadi; Kazem Aghamir, Seyed Mohammad (Frontiers in Genetics, 2022)
Objective: This study explores associations between recurrent kidney stones and genetic polymorphisms. Methods: Meta-analysis of polymorphisms in renal stone cases versus control groups. Four electronic databases (PubMed, SCOPUS, EMBASE, and Web of Science) were searched up to 30 May 2021, using the keywords: “kidney stone” or “kidney calculi,” or “urolithiasis” or “nephrolithiasis” or “urinary calculi” and “genome” or “genetic” or “mutation” or “single nucleotide polymorphism.” Forrest plots, ORs, 95% CI, Chi-square (χ2)-test, and index of heterogeneity (I2) were calculated. Only studies with Newcastle–Ottawa scale (NOS) ≥ 6 were included for quality control, and Funnel, Begg’s, and Eager’s plots assessed publication bias. PROSPERO: CRD42022250427. Results: Among 7,671 searched articles, 72 were included. Polymorphisms in VDR (OR: 1.20; 95% CI: 1.06–1.36), CASR (OR = 1.24; 95% CI: 1.01–1.52), Osteopontin (OR = 1.38; 95% CI: 1.09–1.74), and Urokinase genes (OR = 1.52; 95% CI: 1.02–2.28) showed a significant association with risk of urinary stone formation, while Klotho gene showed a protective effect (OR = 0.75; 95% CI: 0.57–0.99). The VDR gene polymorphism was frequent in Asians, whereas CASR polymorphism was frequent in European and North American populations. Conclusion: Multifactorial nature of the stone formation, emphasizing the role of environmental factors, might explain contradictory results in the literature. While polymorphisms in VDR, CASR, Osteopontin, and Urokinase genes were associated with urinary stone formation, the Klotho gene showed a protective effect.